Lexical Borrowings and Calques From African American Slang in Polish Youth Slang – A Study Based on A Selected Internet Forum - Dylewski, Radosław; Jagodziński, Piotr (Studia Anglica Posnaniensia, 2013)
The aim of the article is to present a very preliminary chunk of a wider study of Polish slang, whose aim is to pinpoint lexical influence of American English in broad terms and the usage and understanding among Polish youngsters of various types of borrowings. More specifically, the authors have concentrated on the borrowings of words, phrases and meanings from a sociolect known as African American English to the language of Polish youngsters. To this end, the largest Polish hardcore punk Internet forum has been scrutinized. The conducted analysis points to a discernible, albeit not significant lexical influence of the sociolect on the Polish youth slang, which calls for a more nuanced, survey-based analysis the authors wish to undertake as part of their research project.